LC‐ESI‐MS/MS determination of 4‐methylpyrazole in dog plasma and its application to a pharmacokinetic study in dogs. (25th September 2017) - Chandrasekhar, Devaraj V.; Suresh, Ponnayyan Sulochana; Dittakavi, Sreekanth; Hiremath, Rakesh A.; Bhamidipati, Ravi Kanth; Richter, Wolfgang; Srinivas, Nuggehally R.; Mullangi, Ramesh
Abstract: A simple, specific, sensitive and rapid LC‐ESI‐MS/MS method has been developed and validated for the quantification of 4‐methylpyrazole in dog plasma using N‐ methylnicotinamide‐ d 4 as an internal standard (IS) as per regulatory guidelines. Sample preparation was accomplished through a simple protein precipitation. Chromatographic separation of 4‐methylpyrazole and the IS was performed on a monolithic (Chromolith RP18e ) column using an isocratic mobile phase comprising 0.2% formic acid in water and acetonitrile (20:80, v /v) at a flow rate of 1.0 mL/min. Elution of 4‐methylpyrazole and the IS occurred at 1.60 and 1.56 min, respectively. The total chromatographic run time was 3.2 min. A linear response function was established in the concentration range of 4.96–4955 ng/mL. The intra‐ and inter‐day accuracy and precision were in the ranges 1.81–12.9 and 3.80–11.1%, respectively. This novel method has been applied to a pharmacokinetic study in dogs.